Bringing ‘Such Matters Upon the Stage’: Women Exemplars in A Warning for Fair Women (1599) and Golding’s A Briefe Discourse (1573) - Christensen, Ann C. (Early Theatre, 2024)
This essay argues that the unnamed playwright of the 1599 tragedy A Warning for Fair Women adapts Arthur Golding’s 1573 (rpt 1577) pamphlet to reshape the heroine from a negative example of adultery and the beneficiary of church-induced repentance into a positive model of motherhood and spiritual agency aided by another woman. Missing from Golding’s account, the play’s main source and the fount of subsequent reportage on the murder of George Sanders, is attention to women’s spiritual agency and their friendship. I compare the play and source text to argue that the playwright’s emendations of Golding’s material omit or minimize certain elements, including the moralizing tone, to advance a more positive view of women than critics have recognized.